2014
DOI: 10.1007/s10519-014-9663-9
|View full text |Cite
|
Sign up to set email alerts
|

Antipredator Behavior QTL: Differences in Rainbow Trout Clonal Lines Derived from Wild and Hatchery Populations

Abstract: Variation in antipredator behavior may partially explain the survival differences seen between wild and hatchery trout and salmon. Antipredator behavior is thought to change during the domestication process, along with other traits. Investigations of antipredator behavior could benefit conservation efforts and supplementation programs. Our goal was to characterize the antipredator behavior in clonal rainbow trout lines derived from either wild or hatchery populations and identify genetic loci associated with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…However, few studies have investigated factors affecting personality development and shaping personality traits, as well as the influence of genetic background on personality. Indeed, genes do play a major role in personality, because the two main behavioral strategies (proactive / reactive, Koolhaas et al, 1999) persist over the course of evolution, and some behavioral and/or physiological traits associated with personality are heritable (Fevolden et al, 1993;Dingemanse et al, 2002;Fevolden et al, 2002;van Oers et al, 2004;Wright et al, 2006;Christensen et al, 2014;Millot et al, 2014). In most cases however, personality traits are probably also determined by individual experience (Sih et al, 2004), which has led some to suggest that experience is as important as genetics in shaping behavior and personality (Fox and Millam, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated factors affecting personality development and shaping personality traits, as well as the influence of genetic background on personality. Indeed, genes do play a major role in personality, because the two main behavioral strategies (proactive / reactive, Koolhaas et al, 1999) persist over the course of evolution, and some behavioral and/or physiological traits associated with personality are heritable (Fevolden et al, 1993;Dingemanse et al, 2002;Fevolden et al, 2002;van Oers et al, 2004;Wright et al, 2006;Christensen et al, 2014;Millot et al, 2014). In most cases however, personality traits are probably also determined by individual experience (Sih et al, 2004), which has led some to suggest that experience is as important as genetics in shaping behavior and personality (Fox and Millam, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…At the genetic level, the contribution of regulatory cis factors to patterns of gene expression has been shown to be considerable (Lee et al , ; Schadt et al , ) suggesting that polymorphism among different loci leads to complex regulatory processes that are reflected by gene expression patterns. The physiological and behavioural traits of coping styles have been repeatedly associated with a genetic basis (Øverli et al , ) and recently some genetically characterized isogenic and clonal lines of fish populations have been described for coping style (Christensen et al , ; Millot et al , ) with promising results for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia there was a 70% failure‐rate of reintroduction programmes on sites where predators had been present, while no failures were reported in the U.S.A., although presence of predators were unknown for most of the programmes there. Previous studies on salmonids have shown that hatcheries produce fishes characterized by antipredator behaviours that differ from behaviours of wild conspecifics (Huntingford, ; Sundström et al , ; Biro et al , ; Jackson & Brown, ; Christensen et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior experiences are important in shaping antipredator behaviour in fishes (Kelley & Magurran, 2003), but some behavioural traits can also be inherited (Weber & Fausch, 2003;Christensen et al, 2014). Certain responses fish express when threatened are reflexes (Abrahams, 2006), while other responses are learned (Tinbergen, 1950;Rolls, 2007).…”
Section: Introductionmentioning
confidence: 99%